Effectiveness of Dapavin Concentration as a Fertilization Inhibitor in Productive-Age Mice (Mus musculus L.) - Mikaila Radisti Effendi; Habsari Shavina Prayogo; Arif Kusmianto (Jurnal FARMASIMED (JFM), 2026)
Background: The rat population in Indonesia, both in agricultural areas and urban settlements, is relatively high with a rapid reproductive rate, thereby impacting the agricultural sector and public health. On the other hand, the physiological similarities between rats and humans make them important model animals in biomedical research, including antifertility studies. Aim: This study aims to examine the effectiveness of various concentrations of Dapavin, a combination of bael leaf extract (Aegle marmelos) containing flavonoids, tannins, and alkaloids, as well as the papain enzyme derived from papaya latex (Carica papaya L.), in inhibiting fertilization in productive-age mice (Mus musculus L.).Methods: The research employed a laboratory experimental method using a post-test only control group design consisting of four treatment groups: control (0%), and Dapavin at concentrations of 10%, 20%, and 30%, each consisting of five female mice. Result: Primary data were obtained through direct observation of pregnancy rates, number of embryos, body weight changes, and mating behavior after oral administration of Dapavin for 14 days. The data were then analyzed statistically to determine differences among treatment groups. The results showed that Dapavin administration significantly reduced fertilization success compared to the control group. A decrease in embryo number and birth weight was observed with increasing doses, with the 30% concentration showing the highest inhibitory effect. Conclusion: These findings indicate that Dapavin has potential as an effective, safe, and environmentally friendly natural phytocontraceptive agent.